The Role of Television Media in Shaping Public Perception of Religion - Fransisca, Vika (Sekolah Tinggi Agama Islam Kuningan, 2024)
Analyzing the growth of media in the midst of people's lives gives a role in seeing the role of its presence for life itself. This is important to understand because the existence of the media and the embodiment of the world of communication in people's lives are two interrelated essences. The purpose of this research is how the role of television mass media in shaping public perception of religion. Furthermore, regarding the role of religious leaders using the media in influencing perceptions of religion. This study uses a quantitative approach with a descriptive survey method to identify and measure the influence of television media in shaping public perception of religion. This research obtained the results that in order to create a more varied and innovative religious broadcast package, so that it can invite the interest of viewers, it is necessary to pay attention to the principles of television broadcasting in Islam and several theories of mass communication related to television broadcasting. Islam through its holy book Al-Qur'an recommends that there are some of its adherents (such as television people) who call for goodness and amar ma'ruf nahi mungkar, in a gentle (persuasive), firm and correct way, and by giving lessons or advice (either by speech or behavior).